Compensatory Renal Hypertrophy in Dogs: Single Nephron Glomerular Filtration Rate - Carrière, Serge (1978)
Kidney weight, length of superficial and juxtamedullary proximal tubules, glomerular diameter, kidney filtration rate and PAH clearance, sodium excretion and intrarenal distribution of filtration (with (14)C-ferrocyanide) were measured in the remaining hypertrophic kidneys of dogs 10 days after unilateral nephrectomy. Whereas kidney weight increased to 75 percent of the original total renal mass, proximal tubule length and mean glomerular diameter remained unchanged. PAH and creatinine clearance, and absolute, but not fractional, sodium excretion, rose significantly. The ratio superficial/juxtamedullary filtration rate remained unchanged, indicating parallel increases of filtration in both cortical regions of hypertrophied kidneys.